Portales web educativos y su influencia en el desarrollo cognitivo de los estudiantes de la Unidad Educativa Lcdo. Alberto Maldonado Iturburo ubicado en el cantón Babahoyo Provincia de Los Ríos - Aviles Manzaba, Dario David (2019)
The continuous technological advance means that every day the human being gets involved in the knowledge society, information and communication technologies, within education, has allowed to make a change in education, that is why educational institutions now They have the need to insert technology into their educational processes. This research report is focused on the management and use of educational web portals as pedagogical tools within the cognitive development of students, educational web portals are a set of resources linked to the world of the internet, where both teacher and student have them as learning tools, in order to change the way of carrying out the educational process both inside and outside the institution; Web portals have become a very useful resource for teachers, as they can prepare their classes more dynamically, while students can strengthen what they have learned in the classroom. The results obtained during the investigation made it possible to demonstrate the need to implement a technological tool for the cognitive development of students, in this case the educational web portals can be used by both teachers and students, With the information obtained was made in the approach of the use of the web portal Schoology, a manual was developed which explains everything necessary for the application of this tool within the teaching and learning process.